Genetic relatedness and antimicrobial resistance of Staphylococcus aureus in goats with subclinical mastitis, North Sumatra, Indonesia - SHINTA MUTIA RAMBE MANALU; LISNAWITA LISNAWITA; NEVY DIANA HANAFI; LUTHFI AZIZ MAHMUD SIREGAR (Society for Indonesian Biodiversity, 2026)
Abstract. Manalu SMR, Lisnawita, Hanafi ND, Siregar LAM. 2026. Genetic relatedness and antimicrobial resistance of Staphylococcus aureus in goats with subclinical mastitis, North Sumatra, Indonesia. Biodiversitas 27 (2): d270233. https://doi.org/10.13057/biodiv/d270233. Staphylococcus aureus is widely recognized as a dominant etiological agent of mastitis in dairy goats and is also regarded as a zoonotic pathogen capable of causing a broad spectrum of human infections, including severe and life-threatening conditions. Despite the routine use of antimicrobial agents to control S. aureus infections, increasing resistance to multiple antibiotic classes has substantially reduced treatment effectiveness. This study investigated the isolation and molecular characterization of S. aureus associated with subclinical mastitis in dairy goats (Capra hircus) from Deli Serdang and Serdang Bedagai Regencies, North Sumatra, and evaluated antimicrobial susceptibility against commonly used antibiotics in regional livestock production. Descriptive analysis supported by graphical visualization and phylogenetic reconstruction was applied to assess distribution patterns and genetic relatedness, while statistical comparisons of antimicrobial resistance proportions between regencies were performed using Fisher’s exact test. This study confirms S. aureus as the most frequently bacterium isolated bacterium in CMT-positive samples based on phenotypic and molecular analyses. High resistance to β-lactam antibiotics was observed in both regions. In Deli Serdang, resistance to amoxicillin and penicillin G was detected in 73.8% (31/42) and 71.4% (30/42) of isolates, respectively. Similarly, in Serdang Bedagai, resistance to amoxicillin and penicillin G was found in 69.0% (20/29) and 58.6% (17/29) of isolates. In contrast, tetracycline showed a higher susceptibility profile in both regions. No statistically significant differences were observed between the two regencies for amoxicillin, penicillin G, or tetracycline resistance (p>0.05). Partial 16S rRNA analysis placed the isolates within S. aureus clade, showing high sequence similarity to reference strains reported from Brazil and India. Collectively, these findings provide essential baseline evidence supporting rational antimicrobial selection and continued resistance surveillance in caprine mastitis management.